2022
DOI: 10.3390/vaccines10050654
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Receive a COVID-19 Vaccine and Associated Factors among Older Adults: A Cross-Sectional Survey in Shanghai, China

Abstract: Background: Older individuals have a high risk of morbidity and mortality due to COVID-19, and one of the most effective ways to prevent COVID-19 is vaccination. Little is known about older people’s willingness to receive a COVID-19 vaccine. Therefore, the objective of this study was to assess the acceptance of and factors influencing the intention to receive a COVID-19 vaccination among older adults in Shanghai, China. Methods: A cross-sectional study was conducted among older adults (≥60 years old) in Shangh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
5
12
0
Order By: Relevance
“…Consistent with previous qualitative studies [ 26 , 27 ], “Not feeling in good health” and “Worry about vaccine side effects causing complications” were considered important reasons by 27% and 18% of older participants, respectively, for refusing or delaying receiving COVID-19 vaccines. In our multivariate analysis, both subjective and objective health status, i.e., self-rated health status and number of chronic conditions (or ever hospital admission), respectively, are significantly associated with vaccine resistance and hesitancy among older people, which is consistent with a recent study conducted in Shanghai, an epicenter of the COVID-19 outbreak in China [ 7 ]. Around the time that the COVID-19 vaccines were first rolling out, the widespread misinformation on the side-effects of vaccines such as frequent heart attacks and severe allergies negatively impacted vaccination intent among older people with multimorbidity [ 28 ]; although, a recent Hong Kong study using population-based vaccination records suggested that vaccinated patients have lower risks of adverse events than unvaccinated individuals [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with previous qualitative studies [ 26 , 27 ], “Not feeling in good health” and “Worry about vaccine side effects causing complications” were considered important reasons by 27% and 18% of older participants, respectively, for refusing or delaying receiving COVID-19 vaccines. In our multivariate analysis, both subjective and objective health status, i.e., self-rated health status and number of chronic conditions (or ever hospital admission), respectively, are significantly associated with vaccine resistance and hesitancy among older people, which is consistent with a recent study conducted in Shanghai, an epicenter of the COVID-19 outbreak in China [ 7 ]. Around the time that the COVID-19 vaccines were first rolling out, the widespread misinformation on the side-effects of vaccines such as frequent heart attacks and severe allergies negatively impacted vaccination intent among older people with multimorbidity [ 28 ]; although, a recent Hong Kong study using population-based vaccination records suggested that vaccinated patients have lower risks of adverse events than unvaccinated individuals [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…Studies that have determined the resistance and hesitancy of the older population to be vaccinated are relatively limited [ 3 ]. In contrast to those in other countries or regions with high vaccine acceptance rates, such as the UK (98.7%) [ 6 ], mainland China (90.9%) [ 7 ], and Taiwan (74.9%) [ 8 ], in Hong Kong many older adults who live in the community are resistant and hesitant to receive the COVID-19 vaccine [ 9 ], where a low vaccination take-up rate among older adults due to vaccine resistance or hesitancy is still the major challenge to achieve high levels of vaccination coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al indicated that the practice of prevention behavior among the elderly in China was positively correlated with the scores of knowledge related to COVID-19 [ 23 ]. At different stages of this pandemic, knowledge about COVID-19 and vaccines have contributed to the vaccination willingness of older populations in China, Brazil, Malaysia, Singapore, Colombia, and other countries [ 40 , 41 , 42 , 43 , 44 ]. Therefore, it is of practical significance to improve the understanding of the elderly on their own susceptibility, effectiveness, and safety of vaccines through various publicity and education ways (such as social media, offline lectures, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…A booster vaccination is essential to supplement the decreasing protective efficacy of the vaccine against the emergence of mutated strains, which, in turn, would protect the vulnerable elderly disease populations from infection and development of severe disease and would reduce the socioeconomic burden. Moreover, a booster dose of COVID-19 vaccine re-enforces individual immune responses in the elderly population and enhances the protective effect of the vaccine against a variety of COVID-19 variants, including Delta variant strains [ 13 , 14 , 15 ], providing a scientific basis for booster vaccination. In the process of promoting COVID-19 vaccine booster doses in various countries, older adults over 60 years of age and people with comorbid underlying diseases are the priority groups currently recommended for booster vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaires have also been widely used as a research method in previous studies on the intention to vaccinate the elderly with the initial doses of the COVID-19 vaccine. An existing study has shown that bad health conditions can reduce the willingness of older adults to receive the initial dose of COVID-19 vaccine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%